Lending Rate, Deposit rate and Stock Prices: Evidence from Colombo Stock Exchange. - Koperunthevy, K.; Vijayarani, K. (Adaikalamatha Institute of Management, India, 2012)
The Bank interest rate variables have strong influence on stock market activities. The Colombo Stock Exchange (CSE) shows a rapid growth in recent years and All Share Price Index (ASPI) and Milanka Price Index (MIP) are the evidence for that. Therefore, this study attempts to identify the impact of long –term lending rate, one- year maturity fixed deposit rate on ASPI and MPI of CSE with a monthly observation from January 2005 to October 2011. The Augmented Dickey – Fuller Unit Root test proves that there is no serial correlation among variables. The Mulicollinearity by Variance Inflation Factor (VIF) supported for the regression analysis. The regression results suggest that interest rate variation 21% on ASPI and 21% on MPI, and the F values are significant at 1% level. Therefore, the study concludes that the lending and deposit rates have impact on stock prices indices.
Keywords: Lending rate; Deposit rate; ASPI; MPI; CSE